Pemodelan Hujan Debit Pada Sub Daerah Aliran Sungai menggunakan Program bantu Hec - Hms (Studi Kasus Pada Kanal Duri) - Sitanggang, Gufrion Elmart; Suprayogi, Imam; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Transformation process Rainfall-runoff is a scientific process which very complex. This complexity process cause of two factor, that are Watershed variability sistem  and  input parameter whick has high variability space and time. So for cope with this komplex process used rainfall-runoff modeling. Model that the used expected could approach Watershed  characteristic. A Rainfall-Runoff model is HEC-HMS. HEC-HMS accurate  for modeling the event a moment such as flood. This modeling will be used at the Duri Canal Watershed in this  study divided into 29 cathment area, with total area 448.4624 km2.   The results of the HEC-HMS modeling in 2002 obtained Qp is 1627.3 m3/sec, this output will calibration with HSS Nakayasu method and obtain Qp 1669.32 m3/sec caused by rainfall 150 mm. Whereas for the 2012 HEC-HMS modeling obtained Qp is 1231.7 m3/sec and for calibration HSS Nakayasu method obtained Qp is 1193.55 m3/sec caused by rainfall 107.5 mm. The result showed nearing values. However HEC-HMS and HSS Nakayasu have different peak time (tp). HEC-HMS have tp at the eleventh o’clock whereas HSS Nakayasu method have tp at the fourth o’clock. This different caused devide of cathment area at HEC-HMS modeling. Keywords : Model, Rainfall-Runoff, Calibration, HEC-HMS, HSS Nakayasu